The contribution to future flood risk in the Severn Estuary from extreme sea level rise due to ice sheet mass loss. Issue 11 (4th November 2013) - Quinn, N.; Bates, P. D.; Siddall, M.
<x xml:space="preserve">Abstract</x> [1] In this paper, we assess the risk of future coastal flooding in the Severn Estuary, examining the contribution from low probability extreme sea level rise scenarios resulting from the possibility of increased rates of ice sheet mass loss in the coming century. A simple asymmetric probability distribution is constructed to include sea level rise scenarios of up to 1.9 m by 2100, based on recent assessments of future sea level rise in the UK. A regular sampling procedure, sampling every 1 mm, is used to increase the boundary water levels associated with a current 1:200 year event to force a two‐dimensional hydrodynamic model of coastal inundation to examine the influence of sea level rise on inundation of the Somerset Levels region. From the resulting ensemble of predictions an estimation of risk (conditioned upon the hazard and the probability of occurrence) by 2100 is established. The results indicate that although the likelihood of extreme sea level rise due to rapid ice sheet mass loss is low, the resulting hazard can be large, resulting in a significant (29.7%) increase to the projected risk. These findings clearly demonstrate that uncertainty in future sea level rise, mostly associated with the rate of ice sheet mass loss, is a vital component of coastal flood risk, and therefore, needs to be accounted for by decision makers when considering mitigation policies related to coastal flooding.